CO2 subsurface mineral storage by its co-injection with recirculating water - Eric H. Oelkers; Serguey Arkadakskiy; Zeyad Ahmed; Noushad Kunnummal; Jakub Fedorik; Massimo Marchesi; Mouadh Addassi; Abdirizak Omar; Niccolo Menegoni; Sigurdur R. Gislason; Grimur Bjornsson; Davide Berno; et al. (Nature, 2026)
Abstract Carbon capture and storage (CCS) has the potential to help nations meet their Paris Agreement CO 2 reduction commitments 1,2 . The ability to capture CO 2 within mafic and ultramafic rocks through mineralization of carbon is an example of such a CCS technology 3,4 , but large-scale deployment has yet to be achieved 5,6 . Each geologic environment in the Earth’s crust requires a distinct carbon storage solution. Whereas some regions of the subsurface contain saline aquifers and sedimentary traps suitable for traditional carbon storage through the injection of high-pressure, dense CO 2 below impermeable caprocks, other regions may lack caprocks 5–9 . In these regions, carbon storage is possible through the mineralization of injected water-dissolved CO 2 forming stable carbonate minerals through its reactions with reactive silicate rocks and minerals 6,10,11 . A notable challenge to applying this process at scale is that it can require 20–50 times or more water than the mass of CO 2 stored 12 . Here we report on an industrial-scale pilot project designed to find a carbon disposal solution for western Saudi Arabia. This arid region has large point-source CO 2 emitters, including petroleum refining and desalination facilities, but lacks saline aquifers and sedimentary traps 13–17 . We find that a CO 2 injection approach based on the recirculation of subsurface fluids can eliminate the need for external water. Our results demonstrate the feasibility of carbon mineral storage in regions in which access to water resources may be limited.